The Social and Cultural Values Transmission of An Oral Tradition - Luluk Ulfa Hasanah; Novi Andari (Indonesian Journal of Social Research (IJSR), 2020)
The purpose of this research is to explore the oral traditions that exist in the Becirongengor village as well as the social and cultural values ​​contained in these oral traditions so that these values ​​can provide learning for the local community. Starting from the problem that the oral tradition that develops in society is starting to lose its existence. Currently the role of oral tradition has begun to be replaced by the existence of social media that has mushroomed in the community. The question is how the oral tradition is able to provide social and cultural values ​​among the community, especially the Becirongengor Village community. The qualitative descriptive method is the chosen research method. The results found that there are still oral traditions that develop in the community, namely (1) the history of Beciro and Ngengor; (2) Haul Mbah Janten and Mbah Surogati; (3) the Kleman Tradition; (4) Paseban Karang Jiwo; (5) MBET traditions; and (6) Slametan. The social and cultural values ​​implicit in the oral tradition are the values ​​of mutual cooperation, andap ashor, tepo seliro, aji mareng sesepuh, friendship, tolerance, religious, and historical values. Of course, oral tradition also provides benefits in social science and cultural education among people, who have experienced the process of transmitting social values ​​that function for entertainment, reminiscing about the past (meaning to history studying), solidarity and togetherness, religious or religious functions, social control, and education.